Preparation method of acid-resistant reverse osmosis membrane with gradient cross-linked structure
By constructing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure on an ultrafiltration base membrane through continuous interfacial polymerization of diamines, the problem of easy acid degradation of polyamide structures in existing technologies is solved, achieving high-efficiency separation performance and a simplified preparation process, thus meeting industrial needs.
Patent Information
- Application Number
- CN202511514256.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2025-12-23
AI Technical Summary
Existing reverse osmosis membranes are prone to acid degradation in acidic environments due to the polyamide structure of the separation layer and the base membrane, resulting in reduced separation performance and service life. Furthermore, the multilayer interfacial polymerization process is complex and cannot meet the industrial demands for high rejection rates and water flux.
A highly cross-linked framework was constructed on an ultrafiltration membrane using a continuous interfacial polymerization method with diamines, and an acid-resistant reverse osmosis membrane with a gradient cross-linked structure was formed through multiple interfacial polymerizations. This simplified the process and improved the density and uniformity of the separation layer.
This study improved the separation performance of polysulfonamide membranes in acidic environments, simplified the preparation process, reduced costs, and met industrial requirements for high sodium chloride rejection and water flux.
Smart Images

Figure CN121177972A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of reverse osmosis membrane technology, and more specifically to a method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure. Background Technology
[0002] Acids play multiple roles in chemical, metallurgical, mining, and resource recycling industries, serving as raw materials, catalysts, and solvents. With rapid industrial development, the generation of acidic wastewater is increasing annually. This wastewater contains large amounts of high-concentration waste acid and heavy metal ions, posing a significant threat and posing a major challenge for treatment. Traditional "neutralization-precipitation-flocculation" methods for treating acidic wastewater consume large amounts of alkali and generate secondary solid waste, resulting in high operating costs and low resource utilization, making it difficult to meet increasingly stringent emission standards and carbon emission targets. Therefore, developing energy-efficient and high-efficiency methods for treating acidic wastewater is urgently needed. Membrane separation technology offers advantages such as high separation efficiency, energy saving and environmental friendliness, small footprint, and a mild operating environment, and is already widely used for treating industrial wastewater.
[0003] Currently, the reverse osmosis membranes commonly used in membrane separation technology are basically polyamide film composite membranes prepared by interfacial polymerization of organic amines as aqueous phase monomers and organic acyl chlorides as oil phase monomers on a base membrane. However, in acidic environments, the polyamide structure of the separation layer and the polyester nonwoven fabric layer in the base membrane are highly susceptible to acid degradation, which greatly reduces the separation performance and service life of the membrane. In recent years, significant progress has been made in the research of acid-resistant membranes. Among them, the polysulfonamide structure exhibits excellent acid resistance due to its stronger steric hindrance effect because the bond angle of the NSC bond (109°) is smaller than that of the NCC bond (120°) of polyamide; while polyethylene base membranes are prepared by melt stretching-hot pressing process, do not contain easily acid-degradable polyester nonwoven fabric, and have the advantages of strong acid resistance and low cost, and are regarded as ideal substrates for acid-resistant membranes. However, two major bottlenecks currently restrict the development of acid-resistant polyvinyl sulfonamide membranes: on the one hand, naphthalene-based sulfonyl chloride monomers have low reactivity, making it difficult to construct a dense and defect-free separation layer in a single step; on the other hand, the polyethylene substrate prepared by the melt-stretch method has a large and uneven pore size, making it difficult for aqueous monomers to be deposited uniformly, easily forming micropore defects, which limits desalination performance. Existing research reports that the highest sodium chloride rejection rate for polyvinyl sulfonamide membranes is about 93%, which is still insufficient to meet the industrial requirements of reverse osmosis (>95%).
[0004] Multilayer interfacial polymerization is a method to improve retention rates. Its core mechanism involves adjusting the monomer diffusion rate, reaction kinetics, and crosslinking density to sequentially form polymer layers with gradient chemical compositions, pore structures, or functional properties on the substrate surface. Compared to traditional single-stage interfacial polymerization, this method can achieve precise control over film thickness, surface roughness, and selective permeability by reducing monomer concentration and increasing the number of polymerization stages, providing a new strategy for the design of high-performance separation membranes. However, due to the polymerization process involving more than three stages, the process is complex. Multilayer interfacial polymerization has been attempted to improve the desalination performance of polysulfonamide membranes, but the effects have not been significant, resulting in few reports. Yuan et al. used a multilayer interfacial polymerization method to alternately impregnate the aqueous monomer piperazine and the oil-phase monomer naphthalene-1,3,6-trisulfonyl chloride on a polyethersulfone-based membrane. The optimal polysulfonamide membrane achieved a sodium chloride rejection rate of 95%, approaching that of reverse osmosis membranes, representing the highest reported retention rate, although its water flux was relatively low. However, the substrate used in this work still contained PET nonwoven fabric, and the process was complex, requiring a total of five interfacial polymerization stages to achieve the current effect.
[0005] This invention discloses a method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linking structure. Specifically, a dense separation layer can be obtained through continuous interfacial polymerization of diamines, which improves the separation performance of the polysulfonamide acid-resistant membrane and shows broad application prospects. Summary of the Invention
[0006] To improve the acid resistance of polysulfonamide, this invention prepares a composite membrane on the surface of a base membrane via a simple method using continuous interfacial polymerization of diamines. This method effectively controls the pore size of the separation layer, altering its structure and morphology, thereby improving the performance of the polysulfonamide acid-resistant membrane.
[0007] This invention discloses a method for preparing an acid-resistant reverse osmosis membrane with a gradient crosslinking structure. The method involves first constructing a highly crosslinked framework on an ultrafiltration base membrane through continuous interfacial polymerization of diamines, followed by further densification of the primary separation layer. Compared to other acid-resistant membrane preparation methods, this invention is low-cost, simple to operate, and yields membranes with superior performance.
[0008] A method for preparing an acid-resistant reverse osmosis membrane with a gradient crosslinking structure includes the following steps: (1) Soak the ultrafiltration membrane in isopropanol and wash it; (2) Deposit an aqueous solution of an organic amine containing multifunctional groups onto the surface of an ultrafiltration membrane, let it stand, and then dry it with an air knife; (3) Deposit the organic acyl chloride oil phase solution containing multifunctional groups onto the membrane surface obtained in step (2) and carry out interfacial polymerization reaction. After the reaction, clean the membrane surface with an organic solvent. (4) Place the composite membrane obtained in step (3) in an oven and heat it, then immerse it in deionized water; (5) Deposit the aqueous solution of organic amine containing multifunctional groups onto the surface of the membrane obtained in step (4), let it stand, and then dry it with an air knife; (6) Deposit the organic acyl chloride oil phase solution containing multifunctional groups onto the membrane surface obtained in step (5) and carry out interfacial polymerization reaction. After the reaction, clean the membrane surface with an organic solvent. (7) The composite membrane obtained in step (6) is placed in an oven and heated, and then immersed in deionized water to obtain an acid-resistant reverse osmosis membrane with a gradient cross-linking structure.
[0009] Further, in step (1), the ultrafiltration membrane material includes any one or more of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polypropylene, polyethylene, polyimide, and cellulose acetate.
[0010] Furthermore, the ultrafiltration membrane is obtained by coating a nonwoven fabric, specifically through the following process: dissolving one or more polymers in an organic solvent and stirring thoroughly; allowing the mixture to stand or removing air bubbles under vacuum; coating the polymer solution onto the nonwoven fabric using a doctor blade or a spin coater; placing the nonwoven fabric coated with the polymer solution in a coagulation bath and washing it thoroughly with deionized water to obtain the polymer membrane.
[0011] Further, in steps (2) and (5), the organic amine containing the multifunctional group is one or a combination of two or more of the following: m-phenylenediamine, divinyltriamine, trivinyltetraamine, tetravinylpentamine, polyethyleneimine, 1,4,7,10-tetraazacyclododecane, 1,4,8,11-tetraazacyclotetradecane, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 2,6-dimethylpiperazine, 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, ethylenediamine, and N,N-bis(2-aminoethyl)ethylenediamine; the concentration of the organic amine containing the multifunctional group is 0.1-5 w / v.
[0012] Further, in steps (3) and (6), the organic acyl chloride containing the multifunctional group is one or a mixture of several of the following: 1,3,6-naphthalenetrisulfonyl chloride, 1,3-benzenedisulfonyl chloride, benzenesulfonyl chloride, 4-chlorobenzenesulfonyl chloride, benzylsulfonyl chloride, 2-chlorobenzenesulfonyl chloride, 1,3,6-benzenetrisulfonyl chloride, and 3-chlorobenzenesulfonyl chloride.
[0013] Further, in steps (3) and (6), the solvent of the organic sulfonyl chloride oil phase solution containing multifunctional groups is one or more of n-hexane, cyclohexane, n-heptane, toluene, benzene, isopar G, isopar E, isopar H, isopar L or isopar M, and the concentration of the organic sulfonyl chloride containing multifunctional groups is 0.01-3wt%.
[0014] Furthermore, in steps (3) and (6), the interfacial polymerization reaction time is 10-240 s.
[0015] Furthermore, in steps (4) and (7), the oven heating temperature is 30-80℃ and the heating time is 1-60min.
[0016] The beneficial effects of this invention are: Acid-resistant reverse osmosis membranes with a gradient cross-linked structure can be obtained through continuous interfacial polymerization on the surface of an ultrafiltration base membrane. This method is simple to operate, low in cost, and can improve the performance of polysulfonamide acid-resistant membranes in a short time, showing broad application prospects. Attached Figure Description
[0017] The accompanying drawings are provided to further explain the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is an AFM image of the polyethylene ultrafiltration membrane and the prepared reverse osmosis membrane in Example 1 of the present invention.
[0018] Figure 2 This is a surface SEM image of the polyethylene ultrafiltration membrane and the prepared reverse osmosis membrane in Example 1 of the present invention. Detailed Implementation
[0019] The technical solution of the present invention will be further defined below with reference to specific embodiments, but the scope of protection is not limited to the description. In the following embodiments, after pre-pressurization for 2 hours at 1.5 MPa, 25°C, and 7 LPM, the desalination rate and permeate flux of the prepared reverse osmosis membrane for 2000 mg / L NaCl were tested. The permeate flux of the reverse osmosis membrane is measured in liters per square meter per hour (LMH).
[0020] Example 1: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 2 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.1 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 1 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 18 LMH and a sodium chloride rejection rate of 98.6%.
[0021] exist Figure 1 In the image, (a) is the AFM image of the PE-based membrane, and (b) is the AFM image of the prepared RO membrane. It can be seen that the membrane roughness is significantly reduced. Figure 2 In the image, (a) is a SEM image of the PE-based membrane and (b) is a SEM image of the prepared RO membrane. It can be seen that the construction of the gradient crosslinking structure makes the membrane have a smoother surface.
[0022] Example 2: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 4 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.1 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 3 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 19.5 LMH and a sodium chloride rejection rate of 97.67%.
[0023] Example 3: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 2 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.2 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 3 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 14.55 LMH and a sodium chloride rejection rate of 97.39%.
[0024] Example 4: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 2 w / v% m-phenylenediamine (MPD) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.1 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 1 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from the polyethylene ultrafiltration membrane had a flux of 7.2 LMH and a sodium chloride rejection rate of 96.89%.
[0025] Example 5: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 2 w / v% piperazine (PIP) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.1 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 1 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 15.9 LMH and a sodium chloride rejection rate of 95.81%.
[0026] Example 6: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=1800Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 4 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 3 min, perform interfacial polymerization, pour it out, and clean the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 40.95 LMH and a sodium chloride rejection rate of 95.36%.
[0027] Example 7: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 0.5w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 minutes, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 4 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 3 min, perform interfacial polymerization, pour it out, and clean the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from the polyethylene ultrafiltration membrane had a flux of 21 LMH and a sodium chloride rejection rate of 96.87%.
[0028] Example 8: A method for preparing an acid-resistant reverse osmosis membrane with a gradient cross-linked structure, comprising the following steps: (1) Soak the polyethylene ultrafiltration membrane in isopropanol and wash it with deionized water; (2) Under normal pressure, temperature of 20℃ and relative humidity of 40%, a 1 w / v% polyethyleneimine (PEI, Mw=10000Da) solution was coated on the surface of a polyethylene film, left to stand for 5 min, poured off, and dried with an air knife. (3) Coat the surface of the membrane obtained in step (2) with a 0.1 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 2 min, perform interfacial polymerization, pour it out, and wash the membrane surface with n-hexane. (4) Place the composite membrane obtained in step (3) in an 80°C oven for 5 minutes and immerse it in deionized water; (5) Coat the membrane surface obtained in step (4) with a 4 w / v% trivinyltetramine (TETA) solution, let it stand for 5 min, pour it out, and dry it with an air knife; (6) Coat the surface of the membrane obtained in step (5) with a 0.15 w / v% 1,3,6-naphthalenetrisulfonyl chloride (NTSC) Isopar G solution, let it stand for 3 min, perform interfacial polymerization, pour it out, and clean the membrane surface with n-hexane. (7) Place the composite membrane obtained in step (6) in an 80°C oven for 5 minutes and immerse it in deionized water; The separation performance of the prepared reverse osmosis membrane was tested. The reverse osmosis membrane prepared from polyethylene ultrafiltration membrane had a flux of 19.35 LMH and a sodium chloride rejection rate of 97.58%.
[0029] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for producing an acid-resistant reverse osmosis membrane having a gradient crosslinked structure, characterized by, The method comprises the following steps: (1) soaking the ultrafiltration base film in isopropyl alcohol and washing; (2) depositing an aqueous solution of organic amine containing multifunctional groups on the surface of the ultrafiltration base film, and then blowing dry with an air knife after standing; (3) depositing an oil phase solution of organic acyl chloride containing multifunctional groups on the membrane surface obtained in step (2), and then performing interfacial polymerization reaction, and then cleaning the membrane surface with an organic solvent after reaction; (4) placing the composite membrane obtained in step (3) in an oven for heating, and then soaking in deionized water; (5) depositing an aqueous solution of organic amine containing multifunctional groups on the membrane surface obtained in step (4), and then blowing dry with an air knife after standing; (6) depositing an oil phase solution of organic acyl chloride containing multifunctional groups on the membrane surface obtained in step (5), and then performing interfacial polymerization reaction, and then cleaning the membrane surface with an organic solvent after reaction; (7) placing the composite membrane obtained in step (6) in an oven for heating, and then soaking in deionized water, to obtain an acid-resistant reverse osmosis membrane with a gradient crosslinking structure.
2. The production method according to claim 1, characterized by, In step (1), the material of the ultrafiltration base film includes any one or several of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polypropylene, polyethylene, polyimide, and cellulose acetate.
3. The production method according to claim 2, characterized by, The ultrafiltration base film is obtained by coating on a non-woven fabric, and the specific process is as follows: dissolving a polymer or a mixture of several polymers in an organic solvent, stirring and dissolving thoroughly; standing or vacuuming to remove bubbles; coating the polymer solution on the non-woven fabric with a doctor blade or a film applicator; placing the non-woven fabric coated with the polymer solution in a coagulation bath and washing thoroughly with deionized water to obtain a polymer base film.
4. The method of claim 1, wherein, In steps (2) and (5), the organic amine containing multifunctional groups is one or a combination of more than two of m-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, polyethyleneimine, 1,4,7,10-tetraazacyclododecane, 1,4,8,11-tetraazacyclotetradecane, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 2,6-dimethylpiperazine, 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, ethylenediamine, and N,N-bis(2-aminoethyl)ethylenediamine; the concentration of the organic amine containing multifunctional groups is 0.1-5 w / v%.
5. The preparation method according to claim 1, characterized in that, In steps (3) and (6), the organic acyl chloride containing multifunctional groups is a mixture of one or several of 1,3,6-naphthalene trisulfonyl chloride, 1,3-benzene disulfonyl chloride, benzyl sulfonyl chloride, 4-chlorobenzene sulfonyl chloride, benzyl sulfonyl chloride, 2-chlorobenzene sulfonyl chloride, 1,3,6-benzene trisulfonyl chloride, and 3-chlorobenzene sulfonyl chloride.
6. The method of claim 1, wherein, In steps (3) and (6), the solvent of the oil phase solution of the organic acyl chloride containing multifunctional groups is one or a combination of more than two of n-hexane, cyclohexane, n-heptane, toluene, benzene, isopar G, isopar E, isopar H, isopar L, or isopar M; the concentration of the organic sulfonyl chloride containing multifunctional groups is 0.01-3 w / v%.
7. The preparation method according to claim 1, characterized in that, In steps (3) and (6), the interfacial polymerization reaction time is 10-240 s.
8. The method of claim 1, wherein, In steps (4) and (7), the heating temperature of the oven is 30-80℃, and the heating time is 1-60 min.